UNIT FRACTIONS AND THE ERDÃ–S-STRAUS CONJECTURE - Shannon, Anthony G (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
This note considers some aspects of finite sums of unit fractions, including associated recurrence relations and conjectures in the context of experimental mathematics. Unit fractions provide a unifying theme.